The Effect of Organizational Culture on Employee Performance - Regina Tilikan Zebua; Fatolosa Hulu; Nanny A Bu’ulolo; Ayler B Ndraha (Golden Ratio of Data in Summary, 2024)
This thesis research aims to determine and test the influence of organizational culture on employee performance at the regional public company Tirta umbu drinking water company, Nias district, using quantitative research methods and the data analysis technique used is linear regression analysis. The population in the study were employees of the regional public drinking water company Tirta umbu, Nias district, totaling 60 people and a sample of 60 respondents. The results of the t test show (calculation) that organizational culture (X) is 8,465 and the significance is 0.000. Hypothesis decision-making conditions are accepted or rejected based on their level of significance. If the significance is less than or equal to 0.05 then the hypothesis is accepted. The research results obtained a significance value of 0.000 <0.05. Thus, it can be concluded that variable X (Organizational Culture) has a significant influence on variable Y (employee performance). From the results of the coefficient of determination (R Square), the coefficient of determination obtained from the correlation of variable X and variable Y is 0.553. Thus, it can be concluded that the size of the influence of variable X (Organizational Culture) on variable Y (employee performance) is 55.3%.